Avaliação das atividades antimicrobiana e antioxidante dos óleos essenciais das folhas dos quimiotipos I, II e III de Lippia alba (Mill.) N. E. Brown - Teixeira, Andréa Bessa (2009)
The species Lippia alba (erva cidreira) is widely used in folk medicine. The composition of essential oil varies quantitative and qualitative, leading to the classification of different chemotypes. A rich pharmacological potential is related to the wide variation in chemical composition of these oils, which arouses the interest of researchers in establishing scientific explanations for such activities. The objective of this study was to evaluate the antimicrobial and antioxidant activities of essential oils of chemotype I, II and III, leaves of L. alba, and to investigate their possible relationships with the chemical composition of their essential oils. The chemical characterization of constituents of essential oils was performed using GC-MS by determining the percentage of constituents present in the samples. The antimicrobial activity of oils was determined by agar diffusion, and MIC and CLM methods by microdilution broth culture and plated on agar, respectively. The antioxidant activity was assessed by measurement of TBARS and by determining the activity of removal of free radicals by DPPH. Essential oils from leaves of L. alba were recognized by the presence of its major constituents in chemotype I (citral-myrcene), chemotype II (citral-limonene) and chemotype III (carvone-limonene). The three essential oils showed activity against S. aureus, even resistant, and C. albicans. For Gram-negative bacteria, the three chemotypes present action on the A. lwoffi; the chemotypes II and III inhibited the growth of A. baumannii, and only the chemotype II was that acted on E. coli ATCC 10536. The lowest MIC obtained for CLM and essential oils of chemotypes I, II and III were 0,312 and 0,625mg/mL, 0,312 and 0,312mg/mL and 0,625 and 0,625mg/mL, respectively. The diffusion technique in agar served as a preliminary step in determining the antimicrobial activity and MIC determination by broth dilution accompanied by reading of optical densities of cultures showed absorbance values similar to the positive control group by a certain concentration and then increased indicating a higher microbial growth. Three chemotypes of OELA reduced lipid peroxidation induced in the hippocampus and brain of rats, but showed no scavenging activity of free radicals measured by the DPPH test. Thus, the results suggest that essential oils of chemotype I, II and III of L. alba, have excellent antimicrobial activity, especially on S. aureus and C. albicans, whereas the diffusion method is an excellent screening method, the dilution method, by visual inspection and reading of absorbance, in addition to determine the MIC, the CLM and evaluate the kinetics of inhibition of microbial growth, the antioxidant potential shown OELA by the hippocampus and cortex of rats makes these products a potential pharmacological tool in the treatment of neurodegenerative diseases, however, for that additional studies are needed, and that differences in the composition of the oil is a factor to be considered important in studies pharmacological.